Entrepreneurship and the integration of refugees and migrants: A case study of Syrian refugees in Egypt - Kabbani, Riham (AUC Knowledge Fountain, 2018)
The Syrian "Exodus" is the biggest assemblage of refugees affecting not just neighboring countries of Jordan, Lebanon, Iraq, Egypt, and Turkey, comprising 95% of the Syrian refugees, but also European states, following refugees' decisions to undertake the "Death Journey" by crossing the Mediterranean Sea (Pierini & Hackenbroich, 2015). Since the beginning of the Syrian conflict in 2011 the refugee crisis involves at least 11 million Syrians, from which 6.3 million are displaced and 13.5 million are in dire need of humanitarian assistance due to inexorable conditions (Mercy Corps, 2017) Protracted refugees situations take from five to twenty years. Numbers of Syrian refugees, who are hosted in Egypt, are ranging from 500,000 to two million, where only a fraction of them, 115,204, is registered (United Nations High Commissioner for Refugees (UNHCR) , 2017). Despite guarantees for individual considerations by the 1951 Convention and the 1967 Protocol, refugees are usually vulnerable, weary and aid dependent. At the same time, their individual contexts are neglected due to weak and fragmented policies enforcement, dwindling living conditions, legal restrictions and social and economic limitations for their livelihoods. Extant literature on refugees lacks a positive framing as enabling individuals and vital socio-economic and developmental tools. Shifting away from the traditional "refugee warehousing" approach, that denotes mobility restriction, idleness enforcement, aid dependency and incapacitated individuals, where their lives are put on hold in violation to the 1951 Refugee Convention law (Smith, 2006), and following successful case studies of refugees' entrepreneurial tendencies, such as in Dadaab and Kakuma Camps in Kenya and Zaat'ari in Jordan. Entrepreneurship may serve as a source of innovation and a mean of income generation, carrying other non-monetary gains for sustainable livelihoods (Montclos & Kagwanja, 2000). To date, refugee entrepreneurship is a nascent research field that is distinct from ethnic entrepreneurship and migrant entrepreneurship. Among recent studies, Garba, Djafar, & Mansor (2013) and Chrysostome (2010) tackled different aspects for ethnic and migrant communities when they pursue entrepreneurial ventures. Considering that each context has a unique set of challenges, few researchers have attempted to understand the relationship between refugees' entrepreneurial endeavors and their integration in hosting economies. Wauters & Lambrecht (2006) demonstrated qualitatively the entrepreneurship potential and analyzed associated socio-economic impacts of entrepreneurship among refugees in Belgium. In 2008, they assessed quantitatively their motivations and associated challenges (Wauters & Lambrecht, 2008). In another study by Mushaben (2006), it draws interesting findings that Turkish ethnic businesses bridged majority and minority cultures in German cities through their entrepreneurial efforts of "Do-It-Yourself-Integration" (DIY) processes. Consequently, "participatory consciousness" among males, and direct identification with the society for women resulted. Finally, within the third-generation of Turkish migrants, they start businesses outside the food sector and they are more likely to embrace the German citizenship (Mushaben, 2006). This research attempts to shed some light if entrepreneurial activities are enabling tools for integration in hosting communities. Following the administration of twelve in-depth interviews to Syrian refugees in Greater Cairo and by comparing empirical findings with literature, it proved that, as a consequence of disadvantages, that Syrians face in hosting communities, they pushed themselves to pursue entrepreneurship as a self-reliance strategy. Promoting factors of "ethnic-cultural" features, where Syrian businesspersons gain access to ethnic markets, labor and emotional support, enabled them to start first their offerings among their communities to enlarge their economic activities among members of hosting societies, by taking advantage of a common language, familiarity with the culture, and relative peace and stability. It is good to note that generalizations should be avoided in later research, especially when common factors of language proficiency and culture familiarity are missing. Additionally, without macroeconomic support of institutional bodies and policy makers, the sustainability of their economic work opportunities is at risk. Due to institutional voids, organizational and institutional barriers and lack of effective coordination among stakeholders, their political integration is set aside, at least for the short and medium terms. This research makes a theoretical contribution by stating that refugee entrepreneurship has common ethnic-cultural promoting factors as ethnic entrepreneurs with similar motives of "necessity based" migrant entrepreneurs of overcoming disadvantages they face in their daily routines. Their social links were necessary determinants for short-term acculturation through their informal economic activities that are illegal yet legitimate. Entrepreneurship among refugee communities cannot only rely on informal sources that are not replenished, as their economic sustainability and their political integration, as citizens in the hosting society, are both at risk. These findings have implications in better understanding of the dynamics behind refugees' pursuit of economic opportunities; how they maintain them; if they can sustain their endeavors and what performance indicators are used to determine their success following their motivations. As practical implications, recommended solutions are suggested to formalize these interactions for local economies development and refugees empowerment.